2009
DOI: 10.1007/s12032-009-9369-7
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality management for 145 cases of Merkel cell carcinoma

Abstract: The results of the multimodality management of 145 cases of cutaneous Merkel cell carcinoma (MCC) are reported herein. Patient information was obtained from medical records of four Canadian institutions and one French institution. These data included ages, pathological stages, disease sites, histological and treatment details. Cause-specific survival (CSS), overall survival (OS) and disease-free survival (DFS) rates were analyzed by the log-rank and Kaplan-Meier methods. From 1988 to 2007, 145 cases were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…These regimens combine in various ways carboplatin, cisplatin and etoposide, cyclophosphamide with vincristine, doxorubicin, prednisone, bleomycin or 5-fluorouracil. Initial regression is frequent with a response rate up to 75% [38][39][40][41] but of short duration with a median overall survival rate of 9 months and high toxicity in elderly patients. Among these regimens, one of the most frequently used for patients with good performance status is a combination of cisplatin and etoposide (cisplatin 60-80 mg/m 2 IV on day 1 plus etoposide 80-120 mg/m 2 IV on days 1-3 every 21-28 days or carboplatin AUC 5 IV on day 1 plus etoposide 80-100 mg/m 2 IV on days 1-3 every 28 days: (http://www.nccn.org/professionals/physician_gls/pdf/ sclc.pdf).…”
Section: Metastatic Stagementioning
confidence: 99%
“…These regimens combine in various ways carboplatin, cisplatin and etoposide, cyclophosphamide with vincristine, doxorubicin, prednisone, bleomycin or 5-fluorouracil. Initial regression is frequent with a response rate up to 75% [38][39][40][41] but of short duration with a median overall survival rate of 9 months and high toxicity in elderly patients. Among these regimens, one of the most frequently used for patients with good performance status is a combination of cisplatin and etoposide (cisplatin 60-80 mg/m 2 IV on day 1 plus etoposide 80-120 mg/m 2 IV on days 1-3 every 21-28 days or carboplatin AUC 5 IV on day 1 plus etoposide 80-100 mg/m 2 IV on days 1-3 every 28 days: (http://www.nccn.org/professionals/physician_gls/pdf/ sclc.pdf).…”
Section: Metastatic Stagementioning
confidence: 99%
“…40 Twenty-six per cent of patients in this study received chemotherapy as part of their primary treatment, and this was administered as an adjuvant to surgery and radiotherapy. Merkel cell carcinoma has been shown to be chemosensitive, 38,[41][42][43][44] and response rates to carboplatin and etoposide, the two agents used most commonly at our institute, have been reported at 60 per cent. 4,38,41 Our study demonstrated no improvements in locoregional control (Table III) or survival (Table IV) in the cohort of patients who received chemotherapy, even after correcting for diseasespecific factors.…”
Section: Discussionmentioning
confidence: 92%
“…La plupart des séries publiées dans la littérature décrivent le CCM comme une maladie radiosensible et chimiosensible [2,3,[11][12][13][14][15][16][17][18][19][20]. Les données récentes plaident pour une prise en charge multidisciplinaire, incluant chirurgie de la tumeur primitive avec des marges d'exérèse larges, exérèse du ganglion sentinelle et radiothérapie adjuvante dans la plupart des cas.…”
Section: Discussionunclassified
“…Du fait de la rareté de cette pathologie, les études prospectives sur de larges séries sont très difficiles à mettre en oeuvre, et la littérature médicale concernant le CCM est essentiellement composée de petites séries rétrospectives. Le traitement chirurgical avec résection large et complète de la tumeur primitive et la radio- thérapie complémentaire sont généralement acceptés, toutefois, il n'existe pas de consensus international concernant la prise en charge optimale de cette maladie [3]. En effet, les données rapportées dans les séries rétrospectives sont souvent imprécises, en particulier le mode chirurgical et la taille des marges d'exérèse, le traitement adjuvant, la prise en charge de la rechute locorégionale, et les options thérapeutiques restent encore débattues.…”
Section: Introductionunclassified